The Representation of Feminism in "Tomboy" Song Lyrics by Destiny Rogers - Laely Rohmatin Nuriana; Estri Oktarena Ikrarini (JELLT (Journal of English Language and Language Teaching), 2022)
This study deals with the representation of feminism found in “Tomboy” song lyrics by Destiny Rogers. The aims of this study are to find out the kinds of feminism and to find out the portrayal of women in the song lyrics of “Tomboy” by Destiny Rogers. The data in this research were taken from the song lyrics of “Tomboy” sung by Destiny Rogers. This study analyzed the types of feminism by using the theory of feminism by Rosemarie Tong. This study used a qualitative method to discover the result of this research. The result of this study indicated that the writer found 19 data in the lyrics that contain some words or phrases that support 7 types of feminism including liberal feminism, radical feminism, Marxist and socialist feminism, care-focused feminism, psychoanalytic feminism, ecofeminism, and post-modern feminism. In addition, women are portrayed as being dominant, talented, productive, beautiful, tomboy and feminine, wealthy, charming, brave, hard worker, and independent human beings in this song. Thus, the portrayal is in line with the title of the song “Tomboy” which defines women as having a manner consider manly or boyish. Moreover, the song lyrics of “Tomboy” by Destiny Rogers indicate that they support feminism and represent the freedom of women.